2017
DOI: 10.5194/os-2017-28
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arctic Ocean outflow and glacier–ocean interaction modify water over the Wandel Sea shelf, northeast Greenland

Abstract: Abstract. The first-ever conductivity–temperature–depth (CTD) observations on the Wandel Sea shelf in North Eastern Greenland were collected in April–May 2015. They were complemented by CTD profiles taken along the continental slope during the Norwegian FRAM 2014–15 drift. The CTD profiles are used to reveal the origin of water masses and interactions with ambient water from the continental slope and the outlet glaciers. The subsurface water is associated with the Pacific Water outflow from the Arctic Ocean. T… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(38 citation statements)
references
References 38 publications
3
35
0
Order By: Relevance
“…A general conception about the shelf circulation can be deduced from the analysis of the local thermohaline structure. Dmitrenko et al (2017) reported that the shelf waters of the Wandel Sea during winter are mainly comprised of Pacific water (PcW) in the depth range of 20-70 m and warmer Arctic-derived Atlantic water (ArAW) outflowing the Arctic Ocean via the western Fram Strait at greater depths. Within the cold halostad (the layer of weakly stratified salinity below the surface mixed layer; Shimada et al, 2015), represented by PcW, salinity increased from about 30 to 31.5 and temperature decreased from −1.6 to −1.7 • C (Fig.…”
Section: Regional Oceanographic Settings Of the Southern Wandel Sea Smentioning
confidence: 99%
See 4 more Smart Citations
“…A general conception about the shelf circulation can be deduced from the analysis of the local thermohaline structure. Dmitrenko et al (2017) reported that the shelf waters of the Wandel Sea during winter are mainly comprised of Pacific water (PcW) in the depth range of 20-70 m and warmer Arctic-derived Atlantic water (ArAW) outflowing the Arctic Ocean via the western Fram Strait at greater depths. Within the cold halostad (the layer of weakly stratified salinity below the surface mixed layer; Shimada et al, 2015), represented by PcW, salinity increased from about 30 to 31.5 and temperature decreased from −1.6 to −1.7 • C (Fig.…”
Section: Regional Oceanographic Settings Of the Southern Wandel Sea Smentioning
confidence: 99%
“…The bottom topography of Wandel Sea adjacent to the northern FIIC glacier outlets is poorly known, with only depth measurements available from the sparse echosounding and CTD pressure records obtained in 2006, respectively (Nørgaard-Pedersen et al, 2008Dmitrenko et al, 2017). The key feature of bottom topography near the FIIC glacier is a submarine glacier valley with depths increasing from ∼ 130 m (2 km east of the mooring position) to more than 180 m measured about 18 km north of the glacier terminus (Fig.…”
Section: Regional Oceanographic Settings Of the Southern Wandel Sea Smentioning
confidence: 99%
See 3 more Smart Citations